FRAUD PENTAGON MEMPREDIKSI KECURANGAN LAPORAN KEUANGAN PERUSAHAAN INFRASTRUKTUR - Giovan Adhy Prasetya; Jhon Rinendy (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aimed to examine the effect of the fraud pentagon (pressure, opportunity, rationalization, competence and arrogance). The population in this study were infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 periods. This research was a quantitative research method that used secondary data in the form of company annual reports and had complete data for that periods. The sampling technique used purposive sampling by collecting 40 samples from 10 sub-sectors of infrastructure companies with 4 data periods. The data analysis method used descriptive statistics, classical assumption test, t-test statistics with the help of SPSS 26 software. The results found that the fraud pentagon factors had a significant effect on predicting the possibility of fraudulent financial statement, specially on predictors of opportunity and arrogance, but had no significant effect on predictors of pressure, rationalization, and competence. Meanwhile, the fraud pentagon predictor such as pressure, opportunity, rationalization, ability and arrogance cumulatively contributed to 31.2% predicting the probability of fraudulent financial statement, while the rest were not included in this study.